2016
DOI: 10.1186/s13023-016-0451-x
|View full text |Cite
|
Sign up to set email alerts
|

Nation-wide epidemiological study of Japanese patients with rare viral myelopathy using novel registration system (HAM-net)

Abstract: BackgroundAt least one million people are infected with human T-lymphotropic virus type 1 (HTLV-1) in Japan, a small percentage of whom develop HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) or adult T-cell leukemia/lymphoma (ATLL). Patients with HAM/TSP suffer from progressively worsening myelopathic symptoms, such as motor disability and bladder dysfunction, and may become wheelchair-bound or even bedridden.MethodsTo learn more about this rare, debilitating disease, we established the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 57 publications
1
39
0
1
Order By: Relevance
“…It should be noted that not only was this study national in scope, but the data suggest that our patients were a nationally representative sample: demographics and clinical features were similar between this study and our nationwide epidemiological study, in which 74.2% of respondents were female and reported an age of onset of 45 years old, age at diagnosis of 53 years, age at presentation of 63 years, and disease duration of 17 years [30]. Thus, though not without its limitations, our study suggests that PSL effectively slows, stops, or even somewhat reverses the course of HAM/TSP when taken continuously over several years, and we believe our results are applicable to the general HAM/TSP patient population.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…It should be noted that not only was this study national in scope, but the data suggest that our patients were a nationally representative sample: demographics and clinical features were similar between this study and our nationwide epidemiological study, in which 74.2% of respondents were female and reported an age of onset of 45 years old, age at diagnosis of 53 years, age at presentation of 63 years, and disease duration of 17 years [30]. Thus, though not without its limitations, our study suggests that PSL effectively slows, stops, or even somewhat reverses the course of HAM/TSP when taken continuously over several years, and we believe our results are applicable to the general HAM/TSP patient population.…”
Section: Discussionsupporting
confidence: 67%
“…Patients were divided into groups based on period of evaluation; we decided to divide them into BShort-Term^(<3 years) and BLong-Term^(> 3 years) groups because reports indicated that changes in OMDS typically appear over 3 years, meaning that a typical untreated patient evaluated over at least 3 years would be expected to exhibit an increase in OMDS [30].…”
Section: Calculations Variables and Statistical Analysismentioning
confidence: 99%
“…In addition, several studies have reported that the incidence of adverse events, such as dry mouth and constipation, was similar between patients treated with mirabegron and those treated with placebo . However, some studies reported that many HAM/TSP patients suffered from constipation and dry mouth even before treatment . Thus, mirabegron may be more convenient to administer in HAM/TSP patients with OAB than anticholinergic agents.…”
Section: Discussionmentioning
confidence: 99%
“…For clinical course analysis, retrospective data from patients who had enrolled in the Japanese HAM/TSP patient registry called “HAM-net” were used ( Coler-Reilly et al, 2016 ). There were 453 patients registered with “HAM-net” from March 2012 until December 2015 ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…There exists a wide variation in the progression rates of HAM/TSP ( Coler-Reilly et al, 2016 ), which suggests the need for stratified medicine. Some studies have reported a subgroup of patients with rapid progression and another subgroup with very slow progression.…”
Section: Introductionmentioning
confidence: 99%